Understanding The Perceptions And Challenges Of Teachers In The Age Of Technology (Journal of Namibian Studies : History Politics Culture, 2023)
The primary objective of this research endeavour was to delve into the intricate realm of teachers' perceptions and the formidable obstacles they encounter in the context of Jordan, specifically pertaining to the integration of technology within their pedagogical approaches. A purposive sampling technique was employed to carefully select a diverse sample of educators from different educational institutions in Jordan. Data collection was carried out using a meticulously designed questionnaire, ensuring a structured approach. The gathered data underwent comprehensive analysis, employing both descriptive and inferential statistical techniques. The results of the study unveiled a prevailing inclination among educators in Jordan towards embracing technology integration, with a recognition of its advantageous impact on student engagement, motivation, and access to information. Nevertheless, a myriad of obstacles were duly recognized, encompassing intricate technical intricacies, restricted availability of essential resources, insufficiently comprehensive training, curriculum limitations, and a palpable aversion towards embracing change. The findings of the correlation analysis revealed noteworthy associations between teachers' perceptions and the obstacles they encountered, underscoring the profound influence of favourable perceptions on their drive to surmount challenges.